Targeting De Novo Lipogenesis and Cholesterol Biosynthesis Simultaneously is a Novel Therapeutic Option for Hepatocellular Carcinoma - Liu Q; Dong X (Journal of Hepatocellular Carcinoma, 2021)
Qian Liu,1 Xifeng Dong2 1Tianjin Lung Cancer Institute, Tianjin Medical University General Hospital, Tianjin 300020, People’s Republic of China; 2Department of Hematology, Tianjin Medical University General Hospital, Tianjin 300020, People’s Republic of ChinaCorrespondence: Xifeng DongDepartment of Hematology, Tianjin Medical University General Hospital, Tianjin 300020, People’s Republic of ChinaEmail dongxifeng@sdu.edu.cnAbstract: Hepatocellular carcinoma (HCC) is one of the most common and serious types of cancer in the world. Currently, the treatment options for patients with HCC are limited. Lipid metabolic alterations are being recognized as a therapeutic target in the past few years. De novo lipogenesis has been frequently observed in HCC. Fatty acid synthase (FASN) is the key enzyme of de novo lipogenesis. Previous studies have indicated that loss of FASN suppresses the growth of HCC cells, but it cannot completely prevent HCC formation in vivo. Thus, other mechanisms that can support HCC tumor formation in the absence of de novo lipogenesis maybe existed. In a study recently published in Gut, Che and colleague investigated the functions of Fasn in HCC mouse model and explore the crosstalk between de novo lipogenesis and cholesterol biosynthesis-associated pathway during HCC development. These findings highlight the simultaneous inhibition of de novo lipogenesis and cholesterol biosynthesis as a novel therapeutic and prevention strategy for HCC.Keywords: hepatocellular carcinoma, HCC, cholesterol, fatty acid, lipogenesis, biosynthesis